Complementary Dark and Bright Plasmonic Nanocavities with Controllable Energy Exchange for SERS Sensing. Issue 16 (25th May 2020) - Liu, Feifei; Zhang, Xinping; Mu, Yunyun; Lin, Jing; Wang, Meng; Ma, He
Abstract: A 3D nanocavity array with each unit composed of complementarily arranged downward and upward silver nanoshells is reported. Due to the underneath planar gold film, the two differently oriented nanoshells form alternatively closed and semi‐closed nanocavities, respectively, which support dark and bright resonance modes of localized surface plasmons (LSPs). For the symmetric design of such nanocavities, mutually independent multipolar LSPs are directly excited at normal incidence, so that the near‐field coupling between them is inhibited. However, when the geometrical symmetry is broken by introducing a breach on a common sidewall of the two adjacent nanocavities, strong interaction and consequently energy exchange between them become allowed. As a result, Fano coupling between the dark and bright LSPs is clearly observed as a sharp spectroscopic resonance. The most important feature of such a coupled dark‐ and bright‐plasmon system is that the resonance modes of two different LSPs can be tuned separately, enhancing largely the flexibility of the photophysical performance and controllability. In particular, these features enable promising applications of such structures in single‐molecular detection through fluorescence enhancement, surface enhanced Raman scattering (SERS), and surface plasmon lasers. SERS measurements verify excellent performance of such nanocavity arrays in high‐sensitivity detection of low‐concentration molecules. Abstract : Plasmonic nanocavities are produced periodically by asymmetric silver nanoshells and a planar gold film. Dark ("D ") and bright ("B ") localized surface plasmons are observed in such complementary structures. Fano‐like coupling is responsible for the energy exchange between "D " and "B " modes through the side‐wall breach. Such a design enables strong local‐field confinement and enhancement, facilitating efficient surface‐enhanced Raman scattering sensing.